2016
DOI: 10.18203/2394-6040.ijcmph20160644
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity among women in the reproductive age group in a rural field practice area of a medical college in Mandya district, Karnataka, India

Abstract: Dietary diversity among women in the reproductive age group in a rural field practice area of a medical college in Mandya district, Karnataka, India Shashikantha SK, Sheethal MP*, Vishma BK INTRODUCTIONNutrition is a main component of health and development. 1 All people need a variety of foods to meet requirements for essential nutrients, and the value of a diverse diet has long been recognized. Dietary diversity is a qualitative measure of food consumption that reflects household access to a variety of foods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Additionally, we find that women's diets are particularly lacking in nonstaple food groups like Vitamin A rich fruits and vegetables, dairy, eggs, and GLV. Shashikantha et al 23 too find that while all women consumed starchy staples, 85% consumed pulses and less than 5% consumed egg and meat products in their sample from Karnataka, India.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, we find that women's diets are particularly lacking in nonstaple food groups like Vitamin A rich fruits and vegetables, dairy, eggs, and GLV. Shashikantha et al 23 too find that while all women consumed starchy staples, 85% consumed pulses and less than 5% consumed egg and meat products in their sample from Karnataka, India.…”
Section: Resultsmentioning
confidence: 95%
“…Kavitha et al 22 use data on 3 districts in Telangana and Maharashtra, from the Village Dynamics in South Asia program, and find that the average HDDS ranges between 7 and 9 food groups, out of a total of 12 food groups. Using a different primary data source, Shashikantha et al 23 also find that most women in their sample in Karnataka consumed 5 of 9 food groups, with about 30% of them consuming fewer food groups. In other parts of South Asia DDSs have been as high as 12 out of 13 food groups for households in Nepal 24 (Pellegrini and Tasciotti) and as low as 4 out of 9 food groups for women in Bangladesh.…”
Section: Status Of Dietary Diversity Across Districts Using 24-hour Amentioning
confidence: 97%
“…Thus, the intake of a diverse diet is a cost-effective strategy to overcome this problem (Bhandari et al, 2016). Globally, women in rural areas who consumed a diversified diet had better dietary diversity scores (Shashikantha et al, 2016).Malnutrition poses a variety of threats to pregnant women and efforts to promote the consumption of local nutrient-rich foods are needed (Elder & Ransom, 2003). Moreover, Sub-Saharan Africa is…”
mentioning
confidence: 99%
“…One study of 3600 rural households across three Indian states of Uttar Pradesh, Bihar and Odisha found that ‘on an average, a woman consumes 0.1 to 0.5 fewer food groups as compared to household members (male)’ (Gupta et al, 2020, p. 323) The food women generally skip are the micronutrient rich food groups like meat, poultry, fish, eggs, Vitamin A rich fruits, vegetables and also pulses. All women consumed more starchy staples (Shashikantha et al, 2016). Thus, women were allocated cheap, easily available and nutrient-poor food groups rather than costly and healthy options that were reserved for men in the household.…”
Section: Gender Gap In Household Food Security and Nutritionmentioning
confidence: 99%